Role of Floating Tablet In Oral Drug Delivery System - Kumar, Sumeet; Keerthy, H.S.; Yadav, Rajkumar Prasad (Asian Journal of Pharmaceutical Research and Development, 2021)
Oral delivery of drugs is the most commonly used mode of administration among all the routes explored for the systemic delivery of drugs by numerous different dosage forms. Many components play a significant role in the development of the drug delivery system. Differences in gastric physiology such as pH and motility, have been shown to have important effects on gastric retention time and drug delivery activity in both intra- and inter-subject variability. FDDS focuses on locally active drugs with a narrow stomach absorption window or a narrow upper small intestine absorption window, are unstable in the intestinal or colonic system, and have poor solubility at high pH values.For drugs that are locally active and have a narrow absorption window in the stomach or upper small intestine and which are unstable in the intestinal or colonic setting. FDDS is particularly interesting because it has a low solubility at high pH. The methods for constructing single and multiple unit floating structures. These systems can help with a variety of issues that arise during the production of a pharmaceutical dose.